Radical Issues in Children's Narratives on Eliyas Explains What’s Going On in Palestine - Riza, Haikal; Arifin, Fitra Mutiara Setiani; Amelanda, Cheriel Louange (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
The discourses about childhood and its entanglement with commonly discussed literature significantly impact children’s literature. This is reflected by writers’ drive to raise issues that do not always revolve around normative issues in their works. Lately, critical issues prominent in children’s literature include radical political unrest and social injustice, as exemplified in Zanib Mian’s illustrative book Eliyas Explains What’s Going On in Palestine. Zanib Mian’s work was the focused material object of the research. The research employed a qualitative approach, explicitly utilizing document analysis as the primary method. This study utilized Gerard Genette’s Narratology and Kimberley Reynolds’ theory of Radical Children’s Literature to examine how narrators convey these problematic issues to children’s readers. The analysis revealed that the narrator in “Eliyas” employed an autodiegetic perspective to foster understanding, effectively engaging children by sharing personal experiences and emotions. Furthermore, the radical issue of the Palestinian conflict, which was presented sensitively, profoundly impacted the children’s characters within the story and, by extension, the children’s readers engaging with the story. The novelty of this research lies in discussing radical issues without leaving the narrative dimension in literary works using narratological theory and the notion of radical children’s literature, especially in Zanib Mian’s latest work, which deals with politics and war in Palestine.